2012
DOI: 10.1093/cid/cis697
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Incidence and Antifungal Drug Resistance in Candidemia: Results From Population-Based Laboratory Surveillance in Atlanta and Baltimore, 2008-2011

Abstract: We describe marked shifts in candidemia epidemiology over the past 2 decades. Adults aged ≥65 years replaced infants as the highest incidence group; adjusted incidence has declined significantly in infants. Use of antifungal prophylaxis, improvements in infection control, or changes in catheter insertion practices may be contributing to these declines. Further surveillance for antifungal resistance and efforts to determine effective prevention strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
293
8
13

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(337 citation statements)
references
References 38 publications
23
293
8
13
Order By: Relevance
“…The overall incidence of candidemia was found to be comparable to that of other studies around the world [8,[12][13][14][15][16]. However, the reported incidence rate is higher in hospitals in Latin America and Italy (1.2 to 1.7 episode/1000 admission) and lower in hospitals in Northern Europe (0.01 to 0.08 episode/1000 admission) [17][18][19].…”
Section: Discussionsupporting
confidence: 79%
“…The overall incidence of candidemia was found to be comparable to that of other studies around the world [8,[12][13][14][15][16]. However, the reported incidence rate is higher in hospitals in Latin America and Italy (1.2 to 1.7 episode/1000 admission) and lower in hospitals in Northern Europe (0.01 to 0.08 episode/1000 admission) [17][18][19].…”
Section: Discussionsupporting
confidence: 79%
“…However, Denmark seems to be an outlier, with an annual average incidence of 8.6/100,000 from 2004 to 2009 (13). At the two extremes among western societies, Australia reports a comparatively low rate of 1.8 cases per 100,000 population (31), whereas a recent population-based surveillance study from the United States conducted from 2008 to 2011 showed incidence rates of 13.3 cases/100,000/year in Atlanta and even as high as 26.2 cases/100,000/year in Baltimore (4). Importantly, all the aforementioned studies documented an overall increase in incidence over the course of study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several populationbased surveys in the United States, Canada, Europe, and Australia have reported an increasing incidence. In the United States, the incidence of candidemia has ranged from 6.0 to 13.3/100,000 population per year (4)(5)(6), whereas, at the same time, the incidence rates in most European countries have been lower, ranging from 1.9 to 4.8/100,000/year (7)(8)(9)(10)(11)(12). Exceptionally high incidence of candidemia has recently been reported both in Baltimore, 26.2/ 100,000/year (4), and Denmark, 8.6/100,000/year (13).…”
mentioning
confidence: 99%
“…C. albicans was the dominant cause (62.5%) of CBSI [15,16]. CBSI caused by C. lipolytica and C. lusitaniae were rarely reported and accounted for only 7% of all detected CBSI [17,18] [2,19,20]. These variations in the geographical distribution of CBSI incidence is most probably due to demographic differences or dissimilar patient management.…”
Section: Discussionmentioning
confidence: 99%